Hybrid percutaneous endoscopic gastrostomy (Hybrid PEG) improves patient safety by combining pull-through technique with gastropexy - Kinzel, Tobias Horst; Reich, Viktoria; Schuhmacher, Leonie; Bojarski, Christian; Adler, Andreas; Veltzke-Schlieker, Wielfried; Jürgensen, Christian; Tacke, Frank; Siegmund, Britta; Buchkremer, Juliane; Branchi, Federica; Treese, Christoph (Endoscopy International Open, 2025)
The direct puncture technique has been associated with a better safety profile compared with the classical pull-through technique for insertion of a percutaneous endoscopic gastrostomy (PEG). In this study, the safety of the hybrid PEG technique, combining gastropexy with the pull-through technique, was analyzed in a large retrospective patient cohort.Clinical data from patients undergoing PEG insertion in a high-volume center for endoscopy were included retrospectively between January 2016 and December 2021. Patient characteristics and complication rates were correlated in univariate and multivariate analyses.Data from 351 patients undergoing PEG insertion with the hybrid PEG technique were compared with 145 procedures with the direct puncture technique and 1073 procedures with the pull-through technique. In the group where gastropexy was performed (hybrid PEG and direct puncture), we could not find any significant differences in frequency of major and minor complications. Comparing the pull-through technique with the gastropexy group, we detected a five-fold higher major complication rate and a doubled minor complication rate for the pull-through technique. Multivariate analysis confirmed the protective role of gastropexy, with an odds ratio of 0.166 (0.084–0.329; P < 0.001) for major complications.Hybrid PEG and direct puncture are equally safe PEG insertion techniques, with significantly better safety profiles than the pull-through technique. Despite the retrospective design of the study, these results suggest preferential use of hybrid PEG due to handling.
Keywords: Endoscopy Upper GI Tract; Gastrostomy and PEJ; Quality and logistical aspects; Performance and complications